The Calculation of Life Insurance Premiums with A Multiple-State Model on Critical Illness Insuranceance - Taraly, Millennia; Satyahadewi, Neva; Perdana, Hendra (Jurnal Matematika; Vol 12 No 2 (2022)DO - 10.24843/JMAT.2022.v12.i02.p150, 2023)
Based on data from the Basic Health Research (Riskesdas) in 2018, the risk of critical illness is increasing and is the highest cause of death for Indonesian population. Currently, the cost of treating disease is not cheap, so maintaining health and preparing for the possibility of being diagnosed with a critical illness in the future is an important step. Critical Illness insurance premiums calculation includes cancer, stroke, heart, and diabetes mellitus. The benefits provided are in the form of death compensation, treatment costs when diagnosed with a critical illness, and there are also costs for Angioplasty surgery. Angioplasty surgery is performing when the individual has a serious critical heart condition and must be performed immediately 24 hours after a heart attack. The data information is in the form of the 2019 Indonesian Mortality Table, and the prevalence of critically ill patients with angioplasty surgical conditions. The premium calculation is carriying out for the insured male aged 40 years in good health, interest rate is 3.75%, the premium payment period and the insurance coverage period is 10 years. The annual net premium value obtained is IDR 5,859,788, of which the sum insured is IDR 500,000,000. There are 3 benefits obtained by the insured: (1) The cost of compensation received for Angioplasty surgery is 25% of the sum insured; (2) The cost of treatment compensation that will be given annually until the insurance coverage period ends when the insured is diagnosed with a critical illness, which is 100% of the sum insured minus the cost of compensation in the event of Angioplasty surgery; and (3) The value of compensation for death due to any cause, which is 100% of the sum insured minus the critical illness benefit for Angioplasty surgery